2007
DOI: 10.1002/ajmg.b.30587
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of normal hearing laterality in familial schizophrenic patients and their relatives

Abstract: Dichotic listening (DL) has been used as a tool to investigate possible left cerebral dysfunction in schizophrenia. However, the wide range of DL tests (e.g., words, emotions, sentences) as well as patient groups ("heterogeneity") has introduced several confounders. Assessing relatives of patients with schizophrenia may overcome some of these problems, and may be more useful in determining if loss of functional cerebral laterality in schizophrenia is a state or a trait phenomenon. The fused consonant-vowel DL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Toulopoulou, Chua, Lam, Cheung, Murray and David () assessed healthy family members of schizophrenia patients, along with the patients themselves and healthy controls. Although general DL performance of patients and their family members was significantly lower than of healthy controls, the laterality index (REA) didn't differ significantly between the three groups.…”
Section: Resultsmentioning
confidence: 99%
“…Toulopoulou, Chua, Lam, Cheung, Murray and David () assessed healthy family members of schizophrenia patients, along with the patients themselves and healthy controls. Although general DL performance of patients and their family members was significantly lower than of healthy controls, the laterality index (REA) didn't differ significantly between the three groups.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the only test used for auditory processing evaluation was DL, leading to incomplete evaluation of elements of auditory processing that are essential for everyday communication. Most DL studies showed that the binaural performance of patients was significantly poorer compared to that of healthy subjects [ 6 , 7 , 8 , 9 , 10 , 11 ]. Furthermore, patients with schizophrenia had reduced laterality [ 12 ].…”
Section: Introductionmentioning
confidence: 99%